Nowe obszary aktywności prawodawczej Wspólnoty a cele polityki rolnej - Balcerak, Sebastian (Wydawnictwo Naukowe UAM, 2008)
The permanent and everlasting character of the Treaty objectives of the Common Agricultural Policy has never blocked the evolution of the agricultural acquis and the application of numerous legal instruments. Both the ECJ case-law and the history of secondary law prove the multiplicity of goals and intentions carried out on the internal market of agricultural products and across rural areas of the EC. Further on, the disparities between the Treaty objectives as such and the broad margin of discretion of the EU institutions in the choice of legal instruments implementing the guidelines of primary law do not render any political decision or measure adopted within the CAP legislative process invalid. This is confirmed by the rich literature based on the Court’s findings. However, this does not allow us to leave without a comment the new legislative initiatives of the Community entering completely new areas of activities in the field of agriculture and beyond its scope. These initiatives require a deeper analysis as they are based under the assumption that the agricultural acquis together with its financial background may and should serve the purpose of other policies: i.e. social policy, energy policy, food safety and food habits or even development projects in third countries. At the same time, the recent introduction of new mechanisms from the sphere of crisis management into direct support legal structure complicates the already disordered catalogue of CAP objectives. Such a situation surely brings a new issue into the discussion on the future of the Common Agricultural Policy and thus demands an appropriate comment.

La stabilitá degli obiettivi della política agricola dell’Unione Europea dettata dal Trattato non ha mai ostacolato la lunga evoluzione del diritto agrario comunitario, evoluzione caratterizzata dall’adozione di numerosi provvedimenti. Sia la giurisprudenza della Corte di Giustizia che il diritto derivato comprovano la molteplicitá degli obiettivi realizzati nell’ambito del mercato unico dei prodotti agricoli e nelle zone rurali della Comunitá. D’altra parte la discordanza tra gli obiettivi della Política Agricola Comune e la liberta degli organi legislativi della Comunitá nello scegliere gli strumenti per la realizzazione dei singoli principi del diritto primario non mettono in discussione la legitimitá delle decisioni politiche prese e degli atti normativi adottati nell’ambito del processo decisionale della PAC. Ció é confermato anche dalla ricca letteratura in materia supportata dalla giurisprudenza della Corte. La suddetta regolaritá e il sempre piú complesso contesto giuridico-economico dell’attivitá agrícola non sono tuttavia sufficient! per esentare da critiche le succesive iniziative legislative ed extra-legislative della Comunitá che occupano nuove aree dell’attivitá legislativa in materia dell’agricoltura e non solo. Ció specialmente se il punto di partenza per le singóle proposte é la convinzione che gli strumenti e la base finanziaria della política agrícola possono, o devono, servire alia realízzazione degli obiettivi della política sociale, energetica, di sicurezza alimentare e di alimentazione o degli obiettivi economici dei paesi terzi. In piü, l’introduzione nella legislazione agrícola europea dei nuovi meccanismi propri della política di gestione delle crisi e la loro collocazione nella struttura di pagamenti diretti rende ancora piü complesso il giá poco coerente elenco degli obiettivi della PAC. Tale situazione, che deve essere presa in considerazione, sicuramente arricchisce il dibattito sul futuro della PAC.
New areas of community's legislative activity and the goals of agricultural policy
Nuove aree di attivitá legislativa della comunitá e gli obiettivi della politica agricola